Impact of Underwater Aging on the Volatile and Phenolic Compounds of Campania Wine-Based Liqueurs “Elixir Falernum” - Andrea Balivo; Giovanni D’Auria; Pasquale Ferranti; Alessia Cepollaro; Salvatore Velotto; Raffaele Sacchi; Alessandro Genovese (Beverages)
Underwater aging of alcoholic beverages has gained growing interest in recent years as a novel strategy for product differentiation. This study investigated the effects of 12 months of underwater aging at 13 m depth on the chemical, volatile, and phenolic profiles of wine-based liqueurs, compared to traditional cellar aging. Individual bottles were analysed using an E-nose, achieving 96% correct classification in the cross-validated confusion matrix. Chemical analysis revealed no significant differences in pH, ethanol content, total and volatile acidity. Although total phenolic content did not differ significantly, underwater-aged liquors exhibited higher levels of anthocyanins, suggesting reduced degradation of phenolic compounds in the anaerobic underwater environment. This was supported by higher levels of free alpha-amino nitrogen and total proteins, suggesting slower oxidation. As a result, underwater-aged liquors showed a lower b* index (yellowness), likely due to the reduced oxidation of red colour compounds. Underwater aging induced some changes in the volatile profile, with a significant increase in certain furanones and pyranones, such as 5-hydroxymethylfurfural, 4-hydroxydihydro-2-(3H)-furanone and 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one, responsible for strawberry, toasted, and caramel notes. This increased production could be attributed to the unique underwater environment, characterised by oscillating vibrations, blue-green light, lower and more constant temperatures and reduced oxygen levels.